Shape of You: Eye-Tracking and Social Perceptions of the Human Body - Edward Morrison; Marianne Lanigan (Behavioral Sciences, 2025)
Much research has considered how physical appearance affects the way people are judged, such as how body size affects judgements of attractiveness and health. Less research, however, has looked at visual attention during such judgements. We used eye-tracking to measure the gaze behaviour of 32 participants (29 female) on male and female computer-generated bodies of different body mass index (BMI). Independent variables were sex and BMI of the model, area of interest of the body, and the judgement made (attractiveness, healthiness, and youthfulness). Dependent variables were the number and duration of fixations, and Likert ratings. Most visual attention was paid to the chest and midriff, but this pattern differed slightly depending on the judgement being made, and on the BMI of the body. The sex of the body also affected eye-gaze behaviour, possibly because most participants were female. The bodies at the lower end of healthy weight were judged most attractive and healthy, in line with previous research, but the lightest bodies were judged as most youthful. These results suggest that these social judgements cue similar but subtly different gaze behaviour, and broadly support the “health-and-fertility” hypothesis, that the most attractive bodies are those that indicate evolutionary fitness.